2020
DOI: 10.1016/j.physa.2020.124491
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in income inequalities and its dynamical origin

Abstract: Individual level and exhaustive income data for Romania (Cluj county) is analysed for several consecutive years. The income distributions collapse on a master-curve when a properly normalised income is considered. The Beta Prime distribution is appropriate to fit the collapsed data. A dynamical model based on a master equation with growth and reset terms is successful in explaining the observed distribution in a self-consistent manner, i.e. the growth and reset rates are evaluated from the same individual leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…For simple growth and reset rates the equation leads to stationary distributions which appear in many complex systems (for a review please consult [ 5 ]). Recent applications are simple but powerful theories for explaining scientific citation and Facebook share dynamics [ 6 ] or income distributions in modern societies [ 7 ]. It has been also proved that the proposed system converges to these stationary distributions independently of the initial condition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For simple growth and reset rates the equation leads to stationary distributions which appear in many complex systems (for a review please consult [ 5 ]). Recent applications are simple but powerful theories for explaining scientific citation and Facebook share dynamics [ 6 ] or income distributions in modern societies [ 7 ]. It has been also proved that the proposed system converges to these stationary distributions independently of the initial condition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other PDFs have been suggested to describe income or wealth distributions in terms of time [ 17 , 26 , 27 , 28 , 29 ]. Many of them are not treatable analytically, so the relation can only be explored numerically.…”
Section: Discussionmentioning
confidence: 99%
“…For part of the PDF, exponential fits can also be done [ 16 ]. As an overall fit to the whole income distribution curve recently, it has been shown that a Tsallis–Pareto cut power-law or some special beta prime distribution works well [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, since its introduction, a plethora of empirical investigations have found the Pareto distribution to be consistent with income data. To focus on the most recent related publication, Néda et al [132] used income data from Japan (2015), USA (2013), Russia (2015), Australia (2011), Finland (2017), Hungary (2015) and a county in Romania (2005), fitting a simple and elegant model to them, and identified a beta prime distribution, which has a Pareto tail with tail index ξ = 1/3. The same research team, in a follow-up publication [133], examined the wealth data for the USA and Russia and again reported a Pareto tail.…”
Section: Hyperbolic Background Measure and The Pareto Distributionmentioning
confidence: 99%